2013
DOI: 10.3389/fpls.2013.00531
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of steady state phloem transport with radial leakage of solute

Abstract: Long-distance phloem transport occurs under a pressure gradient generated by the osmotic exchange of water associated with solute exchange in source and sink regions. But these exchanges also occur along the pathway, and yet their physiological role has almost been ignored in mathematical models of phloem transport. Here we present a steady state model for transport phloem which allows solute leakage, based on the Navier-Stokes and convection-diffusion equations which describe fluid motion rigorously. Sieve tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In addition, we found that increasing the membrane hydraulic conductivity values increases pressure profiles because higher inflow led to greater flow through the sieve tube. Previous studies have also shown non‐linear pressure profiles due to radial inflow (Cabrita et al, ; Phillips & Dungan, ) and also report pressure gradient increases due to increased radial water flows. In contrast to the current study, the aforementioned reports seem to show that when radial water flow ceases, pressure gradients are reduced.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, we found that increasing the membrane hydraulic conductivity values increases pressure profiles because higher inflow led to greater flow through the sieve tube. Previous studies have also shown non‐linear pressure profiles due to radial inflow (Cabrita et al, ; Phillips & Dungan, ) and also report pressure gradient increases due to increased radial water flows. In contrast to the current study, the aforementioned reports seem to show that when radial water flow ceases, pressure gradients are reduced.…”
Section: Discussionmentioning
confidence: 84%
“…Water and sugars may therefore be exchanged along the entire route, not just in the source and sink regions (De Schepper et al, ; Sevanto, ; Thompson, ). This may have implications for the regulation of phloem pressure (Sevanto, ; Van Bel, ), and it may also impact pressure and velocity profiles (Cabrita et al, ; Phillips & Dungan, ; Tyree & Dainty, ). Here, we asked how a semipermeable membrane with high water transport capacity would affect the pressure gradient in the sieve tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phloem function and transport have been, and still are [9], an important subject of debate, and while ongoing research provides new insights on phloem traits and its operating principles, it lacks visualization of the fate of carbon inside plants (e.g., [7,10,15,21,53,55,[64][65][66][67]). To improve our knowledge about the ecological implications of xylem and phloem function, as well as their interactions, several missing links need to be deciphered.…”
Section: Opportunities In Plant Research Remain To Be Seizedmentioning
confidence: 99%
“…Aquaporins membrane proteins are present in all living plants, which form a complex permeable to water. In drought conditions aquaporins activity is critical in regulating hydraulic conductivity [23] (structures inspection status of water, particularly during drought by changing the hydraulic conductivity). With moisture deficit aquaporins are phosphorylated to a lesser extent and permeability of membranes for water is reduced.…”
Section: General Remarksmentioning
confidence: 99%